Macro Variable and Investment Decisions Effect on Company Value - RIZQI MAGRHIBI; HELMA MALINI; Eliza, Eliza Fazliyaton Alias (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2021)
Firm value is an investor's perception of a company, which is often associated with stock prices. A high share price indicates a high company value and a low share price indicates a low company value. Firm value is the price that prospective buyers are willing to pay if the company is sold. In other words, the value of the company that is formed through the stock market value indicator, is strongly influenced by investment opportunities, where investment opportunities provide a signal about the company's growth in the future, thereby increasing stock prices as an indicator of company value (signaling theory). The population in this study are companies listed on the IDX on Kompas 100 for the 2015-2019 period. The results of joint or simultaneous hypothesis testing show that there is a relationship between interest rates, exchange rates, economic growth, financial performance, funding decisions and investment decisions on firm value. Partial test results have a negative and insignificant effect on interest rates on firm value, which provides a relationship that when interest rates decrease, firm value will increase